Polystyrene bead foam material with mechanical property and flame retardant property and preparation method thereof

By using composite flame retardant to coat and promote cross-linking reaction, the problems of poor thermal stability and flammability of polystyrene foam materials are solved, and high-performance halogen-free flame retardant and mechanical properties are improved, suitable for high-temperature or fire conditions. Applications under.

CN119490685APending Publication Date: 2025-02-21SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411601421.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing polystyrene foam materials have poor thermal stability, are flammable, and are difficult to achieve effective flame retardant through conventional means, limiting their application in high temperature or fire conditions and posing a potential threat to the safety of building insulation.

Method used

The composite flame retardant is prepared by blending the modified flame retardant intermediate DOPO with an amino group-containing silane coupling agent, and mixing it with expandable graphite. The particle surface promotes cross-linking reaction and forms a stable foam network structure.

Benefits of technology

The high-performance halogen-free flame retardant of polystyrene bead foam material is achieved, which improves its flame retardant efficiency and mechanical properties, and solves the problems of poor compatibility and poor flame retardant of traditional phosphorus-based flame retardant with polystyrene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128421310000111
    Figure BDA0005128421310000111
  • Figure BDA0005128421310000112
    Figure BDA0005128421310000112
  • Figure BDA0005128421310000113
    Figure BDA0005128421310000113
Patent Text Reader

Abstract

The invention provides a polystyrene bead foam material with mechanical property and flame retardant property and a preparation method thereof, the preparation method comprises the following steps: pre-foaming expandable polystyrene beads, dipping in a compound flame retardant, and mechanically stirring to coat the compound flame retardant on the surfaces of the pre-foamed polystyrene beads, thereby obtaining the polystyrene bead foam material with mechanical property and flame retardant property. And finally, carrying out high-pressure foaming on the pre-foamed polystyrene beads coated with the flame retardant, so as to obtain the polystyrene bead foam material with mechanical properties and flame retardance. In the preparation process, the compound flame retardant is utilized to realize load synergy, in-situ condensation and interfacial compatibilization synergy, in the foaming process, a cross-linking reaction is catalyzed and promoted under a high-temperature condition, effective bonding and curing among beads in the foaming process are realized, a stable foam network structure is formed, and the foaming effect is improved. The compound flame retardant has the functions of a cross-linking agent, and fully meets the requirements of related fields on high-performance flame-retardant foam materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame-retardant functional polystyrene foaming materials, and relates to a polystyrene bead foam material having both mechanical properties and flame-retardant properties and a preparation method thereof. Background Art

[0002] In the current field of building insulation, polystyrene (PS) foam materials are widely used due to their light weight and good thermal insulation performance. However, this material has a series of significant defects, especially its poor thermal stability, easy combustion, and difficulty in achieving effective flame retardancy through conventional means. This characteristic not only limits the application of PS foam materials under high temperature or fire conditions, but also poses a potential threat to its safety in the field of building insulation.

[0003] Polystyrene (PS) foam materials can be mainly divided into molded polystyrene foam (EPS) and extruded polystyrene foam (XPS). Since polystyrene foam materials are mainly composed of C and H elements, have a large specific surface area, thin cell walls, and contain a large amount of gas, they are difficult to flame retardant. Therefore, both EPS and XPS are extremely easy to burn. At present, the main flame retardant method is to add brominated flame retardants to the raw materials for blending. As of the end of 2021, hexabromocyclododecane (HBCD) has been completely banned, and methyl octabromoether and brominated SBS have become the main flame retardants for polystyrene foam, but both are brominated flame retardants. When burned, they will release corrosive or toxic and harmful substances such as hydrogen bromide and dioxins, which are extremely harmful to the natural environment and human life and health.

[0004] In order to meet this challenge, researchers are committed to developing halogen-free flame-retardant polystyrene foam materials. Using phosphorus-based flame retardants to replace brominated flame retardants to prepare flame-retardant functional polystyrene foam is an effective measure to avoid bromination. However, the use of phosphorus-based flame retardants to replace halogen-free flame-retardant polystyrene foam materials still faces many difficulties in industrialization. On the one hand, the amount of flame retardant added is usually large, which not only increases the production cost, but also may cause the precipitation of flame retardants in the material due to the poor compatibility of phosphorus-based flame retardants with polystyrene, affecting the overall performance and appearance of the material. In addition, the molecular structure of polystyrene does not contain the element O, so phosphorus-based flame retardants are difficult to achieve a carbonization effect and have poor flame retardant properties. On the other hand, the addition of flame retardants often leads to a significant decrease in the mechanical properties of the material, such as tensile strength, compressive strength, etc., thereby limiting its reliability in practical applications.

[0005] In addition, halogen-free flame-retardant polystyrene foam materials also face many difficulties in the preparation process. For example, the uniformity of flame retardant dispersion, temperature control during processing, and product quality control all need to be properly resolved.

[0006] Therefore, there is an urgent need for a polystyrene foam material with good flame retardancy, good compatibility and high mechanical properties in order to have better industrial application prospects. Summary of the invention

[0007] In order to solve the above-mentioned problems in the prior art, the present invention provides a polystyrene bead foam material having both mechanical properties and flame retardant properties and a preparation method thereof. In the preparation process, the present invention uses a compound flame retardant to achieve load synergy, in-situ condensation, and interface volume expansion synergy to prepare a high-performance halogen-free flame-retardant polystyrene bead foam material. The compound flame retardant used is uniformly coated on the surface of the polystyrene beads. During the foaming process, it catalyzes and promotes the cross-linking reaction under high temperature conditions to achieve effective bonding and curing between the beads during the foaming process, forming a stable foam network structure, so that the compound flame retardant also has the function of a cross-linking agent, which fully meets the demand for high-performance flame-retardant foam materials in the relevant field.

[0008] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0009] The present invention provides a method for preparing a polystyrene bead foam material having both mechanical properties and flame retardant properties, which mainly comprises the following steps:

[0010] (1) pre-foaming expandable polystyrene beads to obtain pre-foamed polystyrene beads;

[0011] The process parameters of the pre-foaming treatment are as follows: pre-foaming pressure of 0.15-0.30 MPa, pre-foaming temperature of 96-108°C, heat preservation of 30-35 minutes, and aging time of 4-24 hours;

[0012] (2) immersing the pre-expanded polystyrene beads obtained in step (1) in a compound flame retardant, and mechanically stirring the compound flame retardant so that the surface of the pre-expanded polystyrene beads is coated with the compound flame retardant to obtain pre-expanded polystyrene beads coated with the flame retardant;

[0013] The preparation method of the composite flame retardant mainly comprises the following steps:

[0014] (I) modifying the flame retardant intermediate DOPO with an amino-containing silane coupling agent to prepare a flame retardant intermediate modified with a silane coupling agent;

[0015] (II) subjecting the flame retardant intermediate modified by the silane coupling agent obtained in step (I) to alcoholysis to prepare an alcoholysis intermediate in a viscous and transparent liquid state;

[0016] (III) mixing the alcoholysis intermediate obtained in step (II) with expandable graphite in a mass ratio of 10:(1.8-2.2), stirring and reacting at a temperature of 80-85° C. for 30-60 minutes to prepare a composite flame retardant;

[0017] (3) The pre-expanded polystyrene beads coated with a flame retardant obtained in step (2) are subjected to high-pressure foaming to obtain a polystyrene bead foam material having both mechanical properties and flame retardant properties.

[0018] In this article, the expandable polystyrene beads in step (1) are commercially available conventional expandable polystyrene (PS) bead raw materials, and usually chemical raw material grade PS bead raw materials can be directly selected and used.

[0019] In this article, the pre-foaming treatment in step (1) is to expand the expandable beads to a certain extent, so that the density of the foam material is lower when it is finally formed and the density gradient is reduced to make the foam uniform. It should be noted that the process parameters of the pre-foaming treatment defined in the present invention are to provide consistency for the size of the pre-foamed polystyrene beads prepared based on the process parameters and the compound flame retardant coating in the subsequent steps, so as to achieve the technical effect claimed in the present invention.

[0020] Generally, the pre-foaming treatment in step (1) is high-pressure foaming like the subsequent steps, but it should be noted that if the pre-foamed polystyrene bead size consistent with the high-pressure foaming under the process parameters can be achieved, those skilled in the art may also adopt other pre-foaming process methods.

[0021] In this article, the pre-expanded polystyrene beads obtained in step (1) are immersed in a compound flame retardant in step (2), wherein the ratio of the pre-expanded polystyrene beads to the compound flame retardant is selected so as to meet the immersion conditions. In order to better illustrate the present invention and provide a technical solution for reference, the pre-expanded polystyrene beads are immersed in the compound flame retardant, and the mass ratio of the pre-expanded polystyrene beads to the compound flame retardant is 1:(0.2~0.4).

[0022] In one of the technical solutions, in order to allow the compounded flame retardant in step (2) to be better coated on the surface of the pre-expanded polystyrene beads, the mechanical stirring is carried out at 80 to 85° C. for 10 to 15 minutes.

[0023] Herein, the amino-containing silane coupling agent in step (I) is a commercially available silane coupling agent containing amino functional groups commonly used in the prior art, for example, any one or more of KH550, KH560, and KH570.

[0024] In this article, the flame retardant intermediate DOPO is modified by an amino-containing silane coupling agent in step (I), and the modification can be performed directly by referring to the relevant literature or product instructions of the selected silane coupling agent.

[0025] In order to better illustrate the present invention and provide a technical solution for reference, in step (I), the flame retardant intermediate DOPO is modified by an amino-containing silane coupling agent. When the amino-containing silane coupling agent is KH560, the flame retardant intermediate DOPO and KH560 are specifically blended in a molar ratio of 1: (1.2-1.4), and stirred at a temperature of 180-185° C. for 6-8 hours. After the time is reached, a transparent liquid flame retardant intermediate modified by a silane coupling agent is obtained.

[0026] In this article, the flame retardant intermediate DOPO, CAS: 35948-25-5, described in step (I) can be directly obtained by purchasing a commercial product.

[0027] In one of the technical schemes, the silane coupling agent modified flame retardant intermediate obtained in step (I) is subjected to alcoholysis in step (II), wherein the alcoholysis is specifically adding the silane coupling agent modified flame retardant intermediate to an ethanol aqueous solution with a mass concentration of 70%, stirring for at least 30 minutes, and then removing the ethanol by rotary evaporation to prepare a viscous transparent liquid alcoholysis intermediate; in order to fully ensure the alcoholysis effect, it is further preferred that the mass ratio of the silane coupling agent modified flame retardant intermediate to the ethanol aqueous solution is 1 / 10.

[0028] It should be noted that if the compound flame retardant obtained in step (III) is not used immediately after preparation, it is advisable to stir at a temperature of 80-85° C. for at least 10 minutes before immersing the pre-expanded polystyrene beads in the compound flame retardant.

[0029] In this article, in step (3), the pre-expanded polystyrene beads coated with a flame retardant obtained in step (2) are subjected to high-pressure foaming to obtain a polystyrene bead foam material having both mechanical properties and flame retardant properties, wherein the high-pressure foaming is a conventional foaming process selection for polystyrene, and those skilled in the art can directly use conventional high-pressure foaming process parameters for polystyrene for foaming.

[0030] In order to better illustrate the present invention and provide a technical solution for reference, the process parameters of the high-pressure foaming in step (3) are: foaming pressure 0.15-0.30 MPa, temperature 115-126° C., and insulation time 40-60 min.

[0031] One of the inventive points of the present invention is that, in view of the poor compatibility of traditional phosphorus-based flame retardants with polystyrene, low flame retardant efficiency, poor compatibility and dispersibility, poor foaming performance and mechanical properties of materials, a new type of compound flame retardant is designed and synthesized. The compound flame retardant has multiple functions such as flame retardancy, load, dispersion and volume expansion. It is liquid at room temperature. Through the synergistic compatibility of multiple flame retardant elements, the organic-inorganic hybrid co-expansion mechanism constructs a solid condensed phase carbon layer, which effectively improves its flame retardant efficiency; in the actual foaming process, the compound flame retardant undergoes a condensation reaction, enhances the interfacial adhesion of polystyrene beads, reduces the migration behavior of flame retardants, and improves the interfacial bonding strength and flame retardant performance of beads; in-situ volume expansion improves the dispersion of flame retardants on the surface of polystyrene beads, heterogeneous nucleation improves the foaming effect, and realizes controllable and adjustable pore structure. In addition, the compound flame retardant introduced at the bead interface also provides the possibility for microwave selective interfacial bonding and foam electromagnetic shielding performance.

[0032] In addition, the present invention will enrich and develop the theoretical and technical system in this discipline. The project will establish the controllable synthesis and load compatibility technology of green flame retardants, break through the in-situ condensation and volume expansion and controllable foaming technology of flame retardants, and prepare high-performance halogen-free flame retardant polystyrene bead foam materials. It will be beneficial to the development of polymer processing theory, flame retardant in-situ condensation and volume expansion theory, promote the molecular structure design of special resin materials, innovate processing modification technology and special equipment, establish the corresponding relationship between flame retardant types, structures and material properties, clarify the flame retardant mechanism of polymers, and provide theoretical guidance for the design and preparation of halogen-free flame retardant polystyrene bead foams with excellent comprehensive performance, which will promote the rapid development and innovation of disciplines and technologies in this field. It breaks through the limitations of existing phosphorus-based flame retardants such as poor compatibility with polystyrene, poor flame retardancy, and deterioration of mechanical properties of foam products, realizes effective replacement of traditional brominated flame retardant HBCD, solves the problems of brominated flame retardants having great environmental impact and endangering human life and health, and promotes and popularizes halogen-free flame retardant and in-situ capacity expansion technology. It is of great significance to the development of new building insulation materials and the promotion of industrial structure optimization and upgrading, and has good social, economic and ecological benefits.

[0033] Herein, the mixing, stirring, aging and impregnation all follow conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge. DETAILED DESCRIPTION

[0034] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0035] The present invention provides a method for preparing a polystyrene bead foam material having both mechanical properties and flame retardant properties, which mainly comprises the following steps:

[0036] (1) pre-foaming expandable polystyrene beads to obtain pre-foamed polystyrene beads;

[0037] The process parameters of the pre-foaming treatment are as follows: pre-foaming pressure of 0.15-0.30 MPa, pre-foaming temperature of 96-108°C, heat preservation of 30-35 minutes, and aging time of 4-24 hours;

[0038] (2) immersing the pre-expanded polystyrene beads obtained in step (1) in a compound flame retardant, and mechanically stirring the compound flame retardant so that the surface of the pre-expanded polystyrene beads is coated with the compound flame retardant to obtain pre-expanded polystyrene beads coated with the flame retardant;

[0039] The preparation method of the composite flame retardant mainly comprises the following steps:

[0040] (I) modifying the flame retardant intermediate DOPO with an amino-containing silane coupling agent to prepare a flame retardant intermediate modified with a silane coupling agent;

[0041] (II) subjecting the flame retardant intermediate modified by the silane coupling agent obtained in step (I) to alcoholysis to prepare an alcoholysis intermediate in a viscous and transparent liquid state;

[0042] (III) mixing the alcoholysis intermediate obtained in step (II) with expandable graphite in a mass ratio of 10:(1.8-2.2), stirring and reacting at a temperature of 80-85° C. for 30-60 minutes to prepare a composite flame retardant;

[0043] (3) The pre-expanded polystyrene beads coated with a flame retardant obtained in step (2) are subjected to high-pressure foaming to obtain a polystyrene bead foam material having both mechanical properties and flame retardant properties.

[0044] In this article, the expandable polystyrene beads in step (1) are commercially available conventional expandable polystyrene (PS) bead raw materials, and usually chemical raw material grade PS bead raw materials can be directly selected and used.

[0045] In this article, the pre-foaming treatment in step (1) is to expand the expandable beads to a certain extent, so that the density of the foam material is lower when it is finally formed and the density gradient is reduced to make the foam uniform. It should be noted that the process parameters of the pre-foaming treatment defined in the present invention are to provide consistency for the size of the pre-foamed polystyrene beads prepared based on the process parameters and the compound flame retardant coating in the subsequent steps, so as to achieve the technical effect claimed in the present invention.

[0046] Generally, the pre-foaming treatment in step (1) is high-pressure foaming like the subsequent steps, but it should be noted that if the pre-foamed polystyrene bead size consistent with the high-pressure foaming under the process parameters can be achieved, those skilled in the art may also adopt other pre-foaming process methods.

[0047] In this article, the pre-expanded polystyrene beads obtained in step (1) are immersed in a compound flame retardant in step (2), wherein the ratio of the pre-expanded polystyrene beads to the compound flame retardant is selected so as to meet the immersion conditions. In order to better illustrate the present invention and provide an embodiment for reference, the pre-expanded polystyrene beads are immersed in the compound flame retardant, and the mass ratio of the pre-expanded polystyrene beads to the compound flame retardant is 1:(0.2~0.4).

[0048] In one embodiment, in order to allow the compounded flame retardant in step (2) to be better coated on the surface of the pre-expanded polystyrene beads, the mechanical stirring is carried out at 80 to 85° C. for 10 to 15 minutes.

[0049] Herein, the amino-containing silane coupling agent in step (I) is a commercially available silane coupling agent containing amino functional groups commonly used in the prior art, for example, any one or more of KH550, KH560, and KH570.

[0050] In this article, the flame retardant intermediate DOPO is modified by an amino-containing silane coupling agent in step (I), and the modification can be performed directly by referring to the relevant literature or product instructions of the selected silane coupling agent.

[0051] In order to better illustrate the present invention and provide an implementation method for reference, in step (I), the flame retardant intermediate DOPO is modified by an amino-containing silane coupling agent. When the amino-containing silane coupling agent is KH560, the flame retardant intermediate DOPO and KH560 are specifically blended in a molar ratio of 1: (1.2 to 1.4), and stirred at a temperature of 180 to 185° C. for 6 to 8 hours. After the time is reached, a transparent liquid flame retardant intermediate modified by a silane coupling agent is obtained.

[0052] In this article, the flame retardant intermediate DOPO, CAS: 35948-25-5, described in step (I) can be directly obtained by purchasing a commercial product.

[0053] In one embodiment, the silane coupling agent modified flame retardant intermediate obtained in step (I) is subjected to alcoholysis in step (II), wherein the alcoholysis is specifically adding the silane coupling agent modified flame retardant intermediate to an ethanol aqueous solution having a mass concentration of 70%, stirring for at least 30 minutes, and then removing the ethanol by rotary evaporation to prepare a viscous transparent liquid alcoholysis intermediate; in order to fully ensure the alcoholysis effect, it is further preferred that the mass ratio of the silane coupling agent modified flame retardant intermediate to the ethanol aqueous solution is 1 / 10.

[0054] It should be noted that if the compound flame retardant obtained in step (III) is not used immediately after preparation, it is advisable to stir at a temperature of 80-85° C. for at least 10 minutes before immersing the pre-expanded polystyrene beads in the compound flame retardant.

[0055] In this article, in step (3), the pre-expanded polystyrene beads coated with a flame retardant obtained in step (2) are subjected to high-pressure foaming to obtain a polystyrene bead foam material having both mechanical properties and flame retardant properties, wherein the high-pressure foaming is a conventional foaming process selection for polystyrene, and those skilled in the art can directly use conventional high-pressure foaming process parameters for polystyrene for foaming.

[0056] In order to better illustrate the present invention and provide an implementation method for reference, the process parameters of the high-pressure foaming in step (3) are: foaming pressure 0.15-0.30 MPa, temperature 115-126° C., and insulation time 40-60 min.

[0057] One of the inventive points of the present invention is that, in view of the poor compatibility of traditional phosphorus-based flame retardants with polystyrene, low flame retardant efficiency, poor compatibility and dispersibility, poor foaming performance and mechanical properties of materials, a new type of compound flame retardant is designed and synthesized. The compound flame retardant has multiple functions such as flame retardancy, load, dispersion and volume expansion. It is liquid at room temperature. Through the synergistic compatibility of multiple flame retardant elements, the organic-inorganic hybrid co-expansion mechanism constructs a solid condensed phase carbon layer, which effectively improves its flame retardant efficiency; in the actual foaming process, the compound flame retardant undergoes a condensation reaction, enhances the interfacial adhesion of polystyrene beads, reduces the migration behavior of flame retardants, and improves the interfacial bonding strength and flame retardant performance of beads; in-situ volume expansion improves the dispersion of flame retardants on the surface of polystyrene beads, heterogeneous nucleation improves the foaming effect, and realizes controllable and adjustable pore structure. In addition, the compound flame retardant introduced at the bead interface also provides the possibility for microwave selective interfacial bonding and foam electromagnetic shielding performance.

[0058] In addition, the present invention will enrich and develop the theoretical and technical system in this discipline. The project will establish the controllable synthesis and load compatibility technology of green flame retardants, break through the in-situ condensation and volume expansion and controllable foaming technology of flame retardants, and prepare high-performance halogen-free flame retardant polystyrene bead foam materials. It will be beneficial to the development of polymer processing theory, flame retardant in-situ condensation and volume expansion theory, promote the molecular structure design of special resin materials, innovate processing modification technology and special equipment, establish the corresponding relationship between flame retardant types, structures and material properties, clarify the flame retardant mechanism of polymers, and provide theoretical guidance for the design and preparation of halogen-free flame retardant polystyrene bead foams with excellent comprehensive performance, which will promote the rapid development and innovation of disciplines and technologies in this field. It breaks through the limitations of existing phosphorus-based flame retardants such as poor compatibility with polystyrene, poor flame retardancy, and deterioration of mechanical properties of foam products, realizes effective replacement of traditional brominated flame retardant HBCD, solves the problems of brominated flame retardants having great environmental impact and endangering human life and health, and promotes and popularizes halogen-free flame retardant and in-situ capacity expansion technology. It is of great significance to the development of new building insulation materials and the promotion of industrial structure optimization and upgrading, and has good social, economic and ecological benefits.

[0059] Herein, the mixing, stirring, aging and impregnation all follow conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge.

[0060] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0061] Example

[0062] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0063] 1. Raw materials

[0064] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, ≥99.0% purity), Shandong Keyuan Biochemical Co., Ltd.;

[0065] 3-Glycidyloxypropyltrimethoxysilane (KH560, 97.0%), Dingsheng Times Technology Co., Ltd. (Sichuan, China);

[0066] Expandable polystyrene (EPS), H-SB, industrial grade, Ningbo Xinqiao Chemical Co., Ltd.;

[0067] Expandable graphite (EG), EG-E300, 80 mesh, industrial grade, Qingdao Yanhai Carbon Materials Co., Ltd.;

[0068] Ethanol deionized water solution was purchased from Dingsheng Times Technology Co., Ltd. (Sichuan, China).

[0069] Example 1

[0070] Embodiment 1 A method for preparing a polystyrene bead foam material having both mechanical properties and flame retardant properties mainly comprises the following steps:

[0071] (1) pre-foaming expandable polystyrene beads to obtain pre-foamed polystyrene beads;

[0072] The process parameters of the pre-foaming treatment are as follows: pre-foaming pressure of 0.15-0.30 MPa, pre-foaming temperature of 108°C, heat preservation for 30 minutes, and curing at room temperature for 12 hours;

[0073] (2) immersing 40 g of the pre-expanded polystyrene beads obtained in step (1) in 10 g of a compound flame retardant, stirring at 80° C. for 10 min to allow the compound flame retardant to coat the surface of the pre-expanded polystyrene beads, thereby obtaining pre-expanded polystyrene beads coated with a flame retardant;

[0074] The preparation method of the composite flame retardant mainly comprises the following steps:

[0075] (I) blending the flame retardant intermediate DOPO and KH560 in a molar ratio of 1:1.3, stirring at 180°C for 6 hours, and obtaining a transparent liquid flame retardant intermediate modified by a silane coupling agent after the time is up;

[0076] (II) adding the flame retardant intermediate modified by the silane coupling agent obtained in step (I) to a 70% ethanol deionized water solution, stirring for 30 minutes, and removing the ethanol by rotary evaporation at 80° C. to obtain a viscous transparent liquid alcoholysis intermediate; the mass ratio of the flame retardant intermediate modified by the silane coupling agent to the ethanol aqueous solution is 1 / 10;

[0077] (III) mixing the alcoholysis intermediate obtained in step (II) with expandable graphite in a mass ratio of 10:2, stirring and reacting at 80° C. for 30 minutes to prepare a composite flame retardant;

[0078] (3) filling the pre-expanded polystyrene beads coated with a flame retardant obtained in step (2) into a mold, and preparing a polystyrene bead foam material having both mechanical properties and flame retardant properties through high-pressure foaming;

[0079] The process parameters of the high-pressure foaming are as follows: foaming pressure of 0.15-0.30 MPa, keeping warm at 120°C for 45 minutes, taking out the mold, letting it stand and cool to room temperature, and then releasing the pressure and demoulding.

[0080] 2. Test methods

[0081] (1) Differential Scanning Calorimetry (DSC) Analysis

[0082] The DSC curve of the foam material sample was recorded using a Q-20 differential scanning calorimeter from TA Company of the United States. First, the temperature was raised from room temperature to 180°C at a rate of 20°C / min, and kept at this temperature for 5 minutes to eliminate the thermal history of the material, then cooled to room temperature at a cooling rate of 10°C / min, and then heated to 180°C for the second time to obtain the heating and cooling DSC curve of the material, and the glass transition temperature of the foam material sample was calculated from the second heating curve.

[0083] (2) Thermogravimetric analysis (TGA)

[0084] The thermal gravimetric analyzer (TGA) of TA Company of the United States was used to test the thermal gravimetric behavior of the samples under programmed temperature increase. The test atmospheres were nitrogen atmosphere and air atmosphere, respectively. The test temperature range was 40-700°C, the heating rates were 5, 10, 15 and 20°C / min, the gas flow rate was 60 ml / min, and the sample mass was 5-10 mg.

[0085] (3) Cone calorimetry (CONE) test

[0086] The British FTT cone calorimeter was used (sample size: 100mm×100mm×15mm, test standard: ISO5660). The sample was placed horizontally, and the thermal radiation power was 35kW / m 2 During the test, the results such as ignition time (TTI), total heat release (THR), heat release rate (HRR), average heat release rate (Average-HRR), peak heat release rate (Peak-HRR), mass loss rate (MLR) and average mass loss rate (Average-MLR) were recorded.

[0087] (4) Scanning electron microscope (SEM) test

[0088] The morphology and structure of the samples were observed using an Inspect F scanning electron microscope produced by FEI Company of the Netherlands with an accelerating voltage of 20 kV.

[0089] The foam material samples were quenched by liquid nitrogen freezing and gold-sprayed on the surface. Then, the pore morphology and pore distribution of the foam material samples and the dispersion of the compound flame retardant were observed using a scanning electron microscope.

[0090] The carbon residue on the ignition surface of the foam material sample after vertical combustion was taken and treated with gold spraying. The carbon residue morphology of the sample was observed using the above-mentioned scanning electron microscope.

[0091] Apparent density (ρ) test of foam material samples: the test standard is ISO 845:2006, the sample volume is v, the sample mass (m) is weighed using an analytical balance, and calculated according to the following formula:

[0092]

[0093] Test of foam material sample expansion ratio (Φ): use the sample apparent density (ρ f ) and the density of the bead material before foaming (ρ p ) to calculate the foaming ratio, the formula is as follows:

[0094]

[0095] Test of cell density (N) of foam material samples: Image Pro software was used to perform statistical processing on the sample SEM images to obtain the average cell diameter and cell density data. Cell density is defined as the number of cells per unit volume and can be calculated using the following formula:

[0096]

[0097] Where n is the number of cells within a certain area A.

[0098] (5) X-ray photoelectron spectroscopy (XPS) analysis

[0099] The carbon residue used for XPS analysis was prepared by carbonization in a muffle furnace, and the carbon residue and the compound flame retardant were subjected to elemental analysis using an AXIS-UTLTRA DLD X-ray photoelectron spectrometer.

[0100] (6) Mechanical properties test

[0101] Compression strength: According to the ISO 844:2007 test standard, the compression performance of the foam material samples was tested using the American INSTRON 5567 universal testing machine. The sample size was 50mm×50mm×30mm, and the compression test rate was 2mm / min.

[0102] Bending strength: According to the ISO 1209-1:2004 test standard, the bending performance of the foam material samples was tested using an American INSTRON 5567 universal testing machine. The sample size was 120mm×25mm×20mm, and the bending test rate was 10mm / min.

[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a polystyrene bead foam material having both mechanical properties and flame retardant properties, characterized in that The main steps include: (1) pre-foaming expandable polystyrene beads to obtain pre-foamed polystyrene beads; The process parameters of the pre-foaming treatment are as follows: pre-foaming pressure of 0.15-0.30 MPa, pre-foaming temperature of 96-108°C, heat preservation of 30-35 minutes, and aging time of 4-24 hours; (2) immersing the pre-expanded polystyrene beads obtained in step (1) in a compound flame retardant, and mechanically stirring the compound flame retardant so that the surface of the pre-expanded polystyrene beads is coated with the compound flame retardant to obtain pre-expanded polystyrene beads coated with the flame retardant; The preparation method of the composite flame retardant mainly comprises the following steps: (I) modifying the flame retardant intermediate DOPO with an amino-containing silane coupling agent to prepare a flame retardant intermediate modified with a silane coupling agent; (II) subjecting the flame retardant intermediate modified by the silane coupling agent obtained in step (I) to alcoholysis to prepare an alcoholysis intermediate in a viscous and transparent liquid state; (III) mixing the alcoholysis intermediate obtained in step (II) with expandable graphite in a mass ratio of 10:(1.8-2.2), stirring and reacting at a temperature of 80-85° C. for 30-60 minutes to prepare a composite flame retardant; (3) The pre-expanded polystyrene beads coated with a flame retardant obtained in step (2) are subjected to high-pressure foaming to obtain a polystyrene bead foam material having both mechanical properties and flame retardant properties.

2. The preparation method according to claim 1, characterized in that: The pre-expanded polystyrene beads are immersed in the compound flame retardant, and the mass ratio of the pre-expanded polystyrene beads to the compound flame retardant is 1:(0.2-0.4).

3. The preparation method according to claim 1, characterized in that: The mechanical stirring in step (2) is performed at 80 to 85° C. for 10 to 15 minutes.

4. The preparation method according to claim 1, characterized in that: The amino-containing silane coupling agent in step (I) includes any one or more of KH550, KH560, and KH570.

5. The preparation method according to claim 1, characterized in that: In step (I), the flame retardant intermediate DOPO is modified by an amino-containing silane coupling agent. When the amino-containing silane coupling agent is KH560, the flame retardant intermediate DOPO and KH560 are specifically blended in a molar ratio of 1: (1.2-1.4), and stirred at a temperature of 180-185° C. for 6-8 hours. After the time is reached, a transparent liquid flame retardant intermediate modified by a silane coupling agent is obtained.

6. The preparation method according to claim 1, characterized in that: In step (II), the flame retardant intermediate modified by the silane coupling agent obtained in step (I) is subjected to alcoholysis, wherein the alcoholysis is specifically adding the flame retardant intermediate modified by the silane coupling agent to an ethanol aqueous solution with a mass concentration of 70%, stirring for at least 30 minutes, and then removing the ethanol by rotary evaporation to prepare a viscous and transparent liquid alcoholysis intermediate.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the flame retardant intermediate modified by the silane coupling agent to the ethanol aqueous solution is 1 / 10.

8. The preparation method according to claim 1, characterized in that: The process parameters of the high-pressure foaming in step (3) are: foaming pressure 0.15-0.30Mpa, temperature 115-126°C, and insulation time 40-60min.

9. The preparation method according to claim 1, characterized in that: If the compound flame retardant obtained in step (III) is not used immediately after preparation, it is preferable to stir the pre-expanded polystyrene beads at a temperature of 80-85° C. for at least 10 minutes before immersing the pre-expanded polystyrene beads in the compound flame retardant.

10. The polystyrene bead foam material having both mechanical properties and flame retardant properties prepared by the method for preparing the polystyrene bead foam material having both mechanical properties and flame retardant properties as claimed in claim 1.

Citation Information

Patent Citations

  • Preparation method and application of expandable polystyrene particle

    CN102140182A

  • Halogen-free flame-retardant polystyrene foam material and preparation method thereof

    CN102675762A

  • Preparation method and application of nano composite flame retardant containing DOPO and delamination graphene

    CN103073749A

  • Polystyrene with high flame retardant property and preparation method thereof

    CN103709431A

  • Flame-retardant polymer foam board sheet based on supercritical carbon dioxide and preparation method of flame-retardant polymer foam board sheet

    CN117343530A